Crystal structure of 3-(adamantan-1-yl)- 4-(4-chlorophenyl)-1H-1,2,4-triazole- 5(4H)-thione - Al-Wabli, Reem I.; El-Emam, Ali A.; Alroqi, Obaid S.; C. S., Chidan Kumar; Fun, Hoong Kun (International Union of Crystallography, 2015)
The title compound, C18H20ClN3S, is a functionalized triazoline- 3-thione derivative. The benzene ring is almost perpendicular to the planar 1,2,4-triazole ring [maximum deviation = 0.007 (1) A ° ] with a dihedral angle of 89.61 (5) between them and there is an adamantane substituent at the 3-position of the triazolethione ring. In the crystal, N—H S hydrogenbonding interactions link the molecules into chains extending along the c-axis direction. The crystal packing is further stabilized by weak C—H interactions that link adjacent chains into a two-dimensional structure in the bc plane. The crystal studied was an inversion twin with a 0.50 (3):0.50 (3) domain ratio.